OC-033 Familial amyloid polyneuropathy: disease phenotype and the role of liver transplantation: the King's College Hospital selection criteria. (23rd September 2015) - Stangou, A J; Rela, M; Wendon, J; Monaghan, M; Banner, N R; Mathias, C J; Heaton, N D; O'Grady, J
Abstract : Introduction: Familial amyloid polyneuropathy (FAP) due to mutations in the transthyretin gene is the most common form of hereditary amyloidosis. The liver is not itself affected by amyloid deposition in FAP, but it is the main source of production of variant transthyretin (TTR). Liver transplantation (LT) is the only available treatment. Methods: 94 patients with FAP associated with 19 different TTR variants, 68 of whom have so far received LT. Evaluation included assessment of gastrointestinal (GI) and genitourinary (GU) systems, and comprehensive neurological and cardiovascular investigations. Patients were categorised as TTR Met30 (58 cases) or non-Met30 variants (36), and in Met30 as early- or late-onset through cut-off age 50 years at presentation. Results: All Met30 cases presented with either peripheral neuropathy or autonomic neuropathy involving the GI tract with gastroparesis, constipation or diarrhoea and malnutrition, and/or the cardiac sympathetic or parasympathetic systems. Cardiac amyloidosis was a rare and late feature. In contrast, 93% of non-Met30 patients had evidence of cardiac amyloid at presentation and peripheral neuropathy was late manifestation. At median follow-up 71 months post LT neurology improved in 88% of Met30 cases, but deteriorated in 71% of non-Met30. Cardiac amyloid progressed in all non-Met30 cases, while echocardiograms stabilised in early-onset Met30. Serial amyloid scintigraphy demonstrated regression or stabilisation of visceral amyloid in 82% of Met30 and all non-Met30 cases, despite concomitant progression of cardiac amyloidosis in the latter. Cumulative survival was 93% in early-onset Met30, 33% in late-onset Met30, and 33% in non-Met30 (p<0.001). On univariate Cox regression analysis, age at LT, TTR variant, cardiac amyloid preoperatively (p<0.01) and polyneuropathy disability (PND) score (p<0.05), were statistically significant risk factors. On multivariate analysis, patient's age was independent pretransplant risk factor (p<0.001), and rapidly progressive amyloid cardiomyopathy independent posttransplant risk factor (p<0.001). Conclusion: Liver transplantation is rational and effective treatment for FAP. Best results in terms of improvement in FAP manifestations and survival after LT were obtained in patients with early-onset TTR Met30 FAP disease. In order to improve outcomes we propose transplant selection criteria which accommodate the phenotypic heterogeneity among different variants and take into account relevant risk factors.